Peningkatan Pemahaman Konsep melalui Team Games Tournament Berbantuan Permainan Kelereng Etnomatematika pada Pembelajaran Matematika Kelas 1 - Amalia, Isna Riska; Zuliana, Eka; Vebriani, Niasari (Lembaga Yasin AlSys, 2025)
The purpose of this research was to find a solution to the problem of low learning outcomes in understanding mathematical concepts of addition and subtraction material, of which 80% had not reached the KKTP and the low level of student activeness. The learning method used is Team Games Tournament (TGT) assisted by ethnomathematics marbles game. This research is a Classroom Action Research (PTK) consisting of cycle I and cycle II to assess the application of TGT. Each cycle consists of (1) Planning; (2) Action; (3) Observing; and (4) Reflection. This research was conducted at SD 2 Jati Wetan with the subject grade 1 students totalling 15 students. Data were collected by test, observation, and documentation. Data analysis used descriptive, and comparative. The research results showed that there was an increase in the average and percentage of students completing KKTP, that was 65.3 (40%) in cycle I to 85.56 (86.67%) in cycle II. The level of learning activeness also increased from 48% in cycle I to 80.8% in cycle II. Thus, the TGT model assisted by the ethnomathematics marbles game is proven to increase students' concept understanding and activeness in addition and subtraction materials in grade 1 elementary school.